A study of the effects of dance/movement therapy on parenting stress and emotions in mothers of children with autism spectrum disorder - Yang, Xiang; Zhan, Xiaomei; Li, Xiafang; Wang, Yuqing; Kuang, Ziwei (Frontiers in Psychiatry, 2025)
ObjectiveCurrently, many scholars are working to improve the core symptoms of children with autism spectrum disorder, while neglecting the mental health of caregivers of children with ASD. This study examined the effectiveness of dance/movement therapy (DMT) in reducing parenting stress in mothers of children with autism spectrum disorder and whether depression and anxiety mediated the effects thereof. MethodsForty mothers of children with autism spectrum disorder were recruited in Nanchang, China, and divided into an experimental group (20) and a control group (20). The subjects were assessed before and after 12 weeks of dance/movement therapy (DMT) using the Parenting Stress Index/Short Form (PSI-SF), Self-Rating Depression Scale (SDS), and Self-Rating Anxiety Scale (SAS) as the assessment tools.ResultsThe results found that parenting stress, depression, and anxiety scores of mothers of children with autism spectrum disorder were significantly reduced after the dance/movement therapy (DMT) intervention.ConclusionThe mediating effects of depression and anxiety were significant, indicating that dance/movement therapy (DMT) is effective in reducing the levels of parenting stress, depression, and anxiety in mothers of children with autism spectrum disorder, and can indirectly play a role in reducing the levels of parenting stress in mothers of children with autism spectrum disorder by reducing their depression and anxiety.